ANDROID MOBILE GAME MEDIA BASED ON EDUTAINMENT STRATEGY ON SPATIAL ABILITY - Khofifah, Khofifah; Risalah, Dewi; Sandie, Sandie (Jurnal Pendidikan Matematika (JUPITEK), 2022)
This study aims to develop an Android Mobile Game Based on Edutainment Strategy for class VII students of SMP Negeri 3 Pontianak who reach the level of validity, practicality, and effectiveness with the borg and gall model. The subjects in this study were students of class VIII SMP as many as 30 students and 3 media and material experts. The instruments used in this study were media expert validation sheets, teacher responses and student responses, and problem solving ability test questions. The results of validation research on Android Mobile Game Based on Edutainment Strategy are media validation with an average value of 94.28% from the three experts in the very good category. The second is the value of practicality, seen from the value of the questionnaire filled out by the teacher and all students who are accumulated so that a percentage of 92.40% is obtained with very practical criteria. Furthermore, the effectiveness, seen from the value of the results of student posttest work with the number of students who completed as many as 20 people out of 30 people and the average value of students calculated by the formula for the average score and percentage with in the overall student score so that a score of 85.20 was obtained based in the school's KKM score of 75, then the average student test results have complete criteria and are classified as very effective.